IMPLEMENTATION OF THE EDUCATION OF THE ISLAMIC CHARACTER THROUGH EXTRACURICULAR ACTIVITIES OF PENCAK SILAT TO ENHANCE THE SELF-EFFICACY OF THE STUDENTS - Hayati, Dini; Idin, Dede (Al-Mubin, 2024)
Islamic character education has become a major focus in modern education to form qualified and responsible individuals. One approach adopted to this was through extracurricular activities in which Penca Silat became an attractive choice to integrate Islamic values and enhance the self-efficacy of pupils. This research aims to explore and analyze the application of Islamic character education through the extracurricular activities of Penca Silat in an effort to improve self-efficacy of pupils at Domas Siliwangi college. Data is collected through participatory observations, in-depth interviews, and analysis of documents related to the extracurricular activities of Penca Silat as well as the development of Islamic character at Domas Siliwangi College. Research results show that the application of Islamic character education through the extracurricular activities of Penca Silat is effective in improving the self-efficacy of pupils. Through physical training, martial skills, and Islamic values instilled, students experience increased self-confidence, ability to overcome challenges, as well as awareness of Islamic moral and ethical values. In conclusion, Penca Silat's extracurricular activities at Domas Siliwangi College can be an effective means to apply Islamic character education and increase self-efficacy of students. Implications of this study are the importance of paying attention to the role of extracurricular activities in building Islamic character and developing the potential of the student in a holistic way. It is hoped that this research can contribute to the development of Islamic character education and educational practices in other educational institutions